Easy-to-Use Chemiluminescent-Based Assay for a Rapid and Low-Cost Evaluation of the Antioxidant Activity of Cosmetic Products - Seyedeh Rojin Shariati Pour; Donato Calabria; Augusto Nascetti; Domenico Caputo; Giampiero De Cesare; Massimo Guardigli; Martina Zangheri; Mara Mirasoli (Chemosensors, 2024)
New cosmetic formulations are continuously requested by the market and the ingredients are constantly evolving. Recently the use of antioxidants has gained success and, in this context, analytical methods able to quickly and easily assess the antioxidant activity of cosmetics would make it possible to carry out analyses on new formulations even within the manufacturing process without the need for specialized laboratories and personnel, thus evaluating directly on-site the effectiveness and the shelf life of products. In this work, a chemiluminescent inhibition assay was developed for determining the total antioxidant activity in cosmetic products. The method was based on the luminol/enhancers/hydrogen peroxide/horseradish peroxidase chemiluminescent system, which generates light signals measurable through simple and compact instrumentation. The formation of the chemiluminescent signal is inhibited by the presence of antioxidant substances while it is restored once all the antioxidant molecules have been oxidized. The time of appearance of the light signal is related to the total antioxidant activity. The assay was carried out exploiting an integrated device comprising a microwell plate coupled with an array of amorphous silicon hydrogenated photosensors enclosed in a mini-dark box. The method was optimized in terms of concentrations and volumes of the required reagents and sample pre-treatment. A calibration curve was generated taking as a reference the antioxidant activity of ascorbic acid obtaining a detection limit of 10 µM. The developed method was applied to cosmetic products currently on the market as well as on spiked samples in order to evaluate the performance of the methods in terms of sensitivity, accuracy, and reproducibility.